2017
DOI: 10.1210/jc.2017-01642
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Sex Steroids on the Bone Health of Transgender Individuals: A Systematic Review and Meta-Analysis

Abstract: In FTM individuals, masculinizing hormone therapy was not associated with significant changes in BMD, whereas in MTF individuals feminizing hormone therapy was associated with an increase in BMD at the lumbar spine. The impact of these BMD changes on patient-important outcomes such as fracture risk is uncertain.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
78
0
3

Year Published

2018
2018
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 102 publications
(83 citation statements)
references
References 33 publications
2
78
0
3
Order By: Relevance
“…Indeed, Wiepjes et al have recently described an increase in lumbar spine (+3.67%), total hip (+0.97%), and femoral neck (+1.86%) BMD in the presence of oestrogen and antiandrogen therapy in a multicenter study including 231 transgender women undergoing CSHT for 1 year. Moreover, a systematic review and meta‐analysis including 392 transwomen revealed an increase in BMD at the lumbar spine, but not at femoral neck, after 12 and 24 months of oestrogen therapy. The increased BMD observed in the first years of CSHT in those studies might have resulted from oestrogen‐mediated filling of the remodelling space, affecting the balance of osteoblast and osteoclast activity and suppressing bone turnover .…”
Section: Discussionmentioning
confidence: 48%
“…Indeed, Wiepjes et al have recently described an increase in lumbar spine (+3.67%), total hip (+0.97%), and femoral neck (+1.86%) BMD in the presence of oestrogen and antiandrogen therapy in a multicenter study including 231 transgender women undergoing CSHT for 1 year. Moreover, a systematic review and meta‐analysis including 392 transwomen revealed an increase in BMD at the lumbar spine, but not at femoral neck, after 12 and 24 months of oestrogen therapy. The increased BMD observed in the first years of CSHT in those studies might have resulted from oestrogen‐mediated filling of the remodelling space, affecting the balance of osteoblast and osteoclast activity and suppressing bone turnover .…”
Section: Discussionmentioning
confidence: 48%
“…(16,32) Although earlier short-term and long-term studies did not show a detrimental effect of HT on BMD, (18,31) higher fracture risk in young trans women compared with age-matched reference women may be explained by lower initial BMD even before start of HT. Earlier studies found that trans women, also at younger ages, had a high prevalence of osteoporosis or low BMD even before hormonal treatment.…”
Section: Discussionmentioning
confidence: 89%
“…Earlier studies found either a maintenance (16)(17)(18)(19)(20) or increase (16)(17)(18)(21)(22)(23)(24)(25)(26) in BMD in both adult trans women and trans men after short-term HT. Earlier studies found either a maintenance (16)(17)(18)(19)(20) or increase (16)(17)(18)(21)(22)(23)(24)(25)(26) in BMD in both adult trans women and trans men after short-term HT.…”
Section: Introductionmentioning
confidence: 91%
“…Gender‐affirming hormonal treatment (HT) in transgender people influences bone metabolism. After 1 year of HT the BMD increases in transwomen (male‐to‐female transgender people), whereas in transmen (female‐to‐male transgender people) a maintenance or increase in BMD is described. More specifically, a larger increase in BMD was found in postmenopausal transmen with estrogen deficiency prior to HT compared with premenopausal transmen with normal estradiol concentrations.…”
Section: Introductionmentioning
confidence: 99%